Acquisition site-based remodelling of Clostridium perfringens- and Clostridioides difficile-related gut microbiota (2023)
Introduction: Clostridium perfringens is a gram-positive, anaerobic sporulating bacillus which can infect several hosts, thereby being considered the causative agent of many gut illnesses. Some studies have suggested that C. perfringens’s virulence factors may negatively affect gut microbiota homeostasis by decreasing beneficial bacteria; however, studies have failed to evaluate the simultaneous presence of other pathogenic bacteria, such as C. difficile (another sporulating bacillus known to play a role in gut microbiota imbalance). Conscious of the lack of compelling data, this work has ascertained how such microorganisms’ coexistence can be associated with a variation in gut microbiota composition, compared to that of C. perfringens colonisation. Methods: PCR was thus used for identifying C. perfringens and C. difficile in 98 samples. Amplicon-based sequencing of 16S- and 18S-rRNA genes’ V4 hypervariable region from such samples was used for determining the microbiota’s taxonomical composition and diversity. Results: Small differences were observed in bacterial communities’ taxonomic composition and diversity; such imbalance was mainly associated with groups having hospital-acquired diarrhoea. Conclusion: The alterations reported herein may have been influenced by C. difficile and diarrhoea acquisition site, despite C. perfringens’ ability to cause alterations in microbiota due to its virulence factors. Our findings highlight the need for a holistic view of gut microbiota